Long non-coding RNA HOTAIR induces the PI3K/AKT/mTOR signaling pathway in breast cancer cells - Sadeghalvad,Mona (2022)
SUMMARY OBJECTIVE: The phosphoinositide 3-kinase/protein kinase AKT/mammalian target of rapamycin signaling pathway is essential for proper cellular metabolism and cell growth. However, aberrant activation of this pathway has been linked to the progression and metastasis of breast cancer. Recently, the role of long non-coding RNAs in interfering with the cell signaling pathways involved in cell growth and metabolism has been identified. HOX antisense intergenic RNA is an long non-coding RNA whose abnormal expression has been associated with development, therapy resistance, and metastasis of breast cancer. The purpose of this study was to investigate whether the long non-coding RNA HOX antisense intergenic RNA is linked to the phosphoinositide 3-kinase/protein kinase AKT/mammalian target of rapamycin signaling pathway in breast cancer cells. METHODS: HOX antisense intergenic RNA was silenced in the breast cancer cell line MCF-7 using siRNAs. Subsequently, the gene expression level of HOX antisense intergenic RNA, PI3K, AKT, and mTOR was assessed using real-time RT-PCR. Also, the 3-(4,5-dimethylthiazol- 2-yl)-2,5-diphenyl-tetrazolium bromide) assay was used to analyze cell proliferation. RESULTS: The results revealed that HOX antisense intergenic RNA knockdown can downregulate the expression of PI3K, AKT, and mTOR RNAs compared to negative control in MCF-7 cells. In addition, the proliferation of breast cancer cells was significantly reduced following the HOX antisense intergenic RNA silencing. CONCLUSION: This study may introduce HOX antisense intergenic RNA as a molecule involved in the upregulation of the phosphoinositide 3-kinase/protein kinase AKT/mammalian target of rapamycin signaling pathway in breast cancer cells that may contribute to breast cancer cell proliferation.